Relevance of Federalism in Nepal - Yadav, Manoj K. (Journal of Development and Administrative Studies, 2025)
There is a narrative among some sections of people across party affiliations that a small country like Nepal does not need federalism and that it only adds financial burden to the nation.  This paper compares Nepal with New England of USA and tries to analyze the causes and needs for federal structure within the two. Nepal and New England are comparable in size and both have diverse demography and geography. The analysis is based on secondary data and the findings based on territorial size, population, ethnic and geographical diversity suggest that Nepal cannot be considered small to align it with unitary state model. Unlike the case of New England whose territorial model of federal structure is rooted to its historical and colonial existence, Nepal’s federal structure is the result of revolutions against historical marginalization of ethnic and backward groups and thus its federal structure aligns with  territorial-multinational hybrid model federalism. Furthermore, the remarkable progress achieved in the sectors of infrastructure, health and higher education during the relatively short span of federalism clearly points towards the practical applicability of federalism in Nepal.